Emerging immunotherapies in osteosarcoma: from checkpoint blockade to cellular therapies - Han, Zhiwei; Chen, Guomin; Wang, Dongchen (Frontiers in Immunology, 2025)
Osteosarcoma remains a highly aggressive bone malignancy with limited therapeutic options, necessitating novel treatment strategies. Immunotherapy has emerged as a promising approach, yet its efficacy in osteosarcoma is hindered by an immunosuppressive tumor microenvironment and resistance mechanisms. This review explores recent advancements in checkpoint blockade, cellular therapies, and combination strategies aimed at enhancing immune responses. We highlight key challenges, including tumor heterogeneity, poor immune infiltration, and the need for predictive biomarkers. By integrating immunotherapy with chemotherapy, radiotherapy, and targeted therapy, emerging approaches seek to improve treatment outcomes. This review provides a comprehensive analysis of the evolving landscape of osteosarcoma immunotherapy, offering insights into future directions and potential breakthroughs. Researchers and clinicians will benefit from understanding these developments, as they pave the way for more effective and personalized therapeutic strategies in osteosarcoma.